Reduced pH and elevated salinities affect the physiology of intertidal crab Minuca mordax (Crustacea, Decapoda) - Strefezza, Tayna Figueiredo [UNESP]; De Andrade, Isabel Marques [UNESP]; Augusto, Alessandra [UNESP] (Taylor & Francis, 2019)
Minuca mordax is a model for studies on ocean acidification and sea-level rise because lives in mangroves and riverbanks with low pH. We investigated the physiology of the crabs exposed to differents pH (6.5 and 5.8) and salinity (25, 30, 35, 40 45S). There was not mortality or alterations in the hypo-osmoregulation, suggesting that the factors did not affect salt absorption/secretion. Reduced pH changed metabolism, ammonia excretion, and hepatosomatic index in relation to the animals kept in control pH. At elevated salinities, metabolism increased when animals were kept in control pH, but it decreased when they were exposed to acidified pH. energy substrate, varied between proteins to a mixture of proteins and lipids. Important physiological parameters, related to the catabolism of amino acids and to the energy demand are changed and the consequences might include alterations in growth and reproduction due to the energy channeling to limiting processes of homeostasis.
Keywords: climate change; fiddler crab; metabolism; Osmoreglation; sea level rise